Evaluación anatomopatológica de piel, músculo y hueso de podocnemis unifilis provenientes del Parque Nacional Yasuní - Vargas Castillo, Diana Carolina (2018)
The yellow-spotted river turtles (Podocnemis unifilis) are currently listed as vulnerable and many of them are in danger of becoming extinct (IUCN, 2017), due to the sale and marketing of their eggs and the adult turtles. The Widlife Conservation Society-Ecuador has currently a conservation program for the species in the Yasuní National Park. This program is responsible for the incubation, the release and the monitoring of the turtles. The present research included a total of 30 Charapa turtles at maximum 3 months of age, and they came from three communities of the Yasuní National Park: Nueva Providencia (n equal 10), Sani Isla (n equal 10) and Kichwa de Indillama (n equal 10). The main objective of this research was to describe the anatomopathological findings of the skin, the bone and the muscle of the Charapa turtles. This study began with an analysis using a stereoscope in order to observe the injuries taken by photos. This was done in the Environmental Laboratory in the Queri headquarter, of the University of America (Ecuador). Relevant lesions were evidenced, such as polydactyly, in (1/30), corresponding to 3.33 por ciento of the turtles. The other relevant finding was a fracture, also corresponding to (1/30) with 3.33 por ciento. It is important to say that, from the population and conservation points of view, these findings are not serious because each lesion was presented in a single animal and this does not compromise the viability of the entire species. Using this study, the learning about the charapa turtles is extended. Additionally, it encourages deeper studies to determine the exact cause of the polydactyly and the fracture.